Effect of design configuration on structural response of longline aquaculture in waves. (February 2021) - Feng, Dejun; Meng, Ang; Wang, Ping; Yao, Yanbo; Gui, Fukun
Abstract: The submerged deep-water longline aquaculture facility is known as a typical, flexible multi-degree-of-freedom offshore structure. Effects of layout concepts of the dropper weight, the upper buoy pattern and the incident wave angle on longline aquaculture systems have been studied by means of numerical modellings and conducting scaled model experiments. The results have showed that the dropper weight and the incident wave angle have significant influence on the motion and loading of the raft-like system. The maximum displacement of the main line is negatively correlated with the dropper weight. The maximum tension of the main line, the downstream mooring line, the upper whip lines and the dropper linesincreases with the increase of the dropper weight. The tension of the upstream mooring line decreases slightly with the increase of the dropper weight. The impact of the upper buoy pattern on the motion and loading of the system is so insignificant as to be ignored. The maximum tension of the mooring lines and the displacement of the long line are positively correlated with structure orientation within the angle range of 0 ° to 60 ° and show negative correlation within the structure orientation of 60 ° to 90 °. The impact of structure orientation on the main line, the upper whip lines and the dropper lines is not so obvious. This study is expected to benefit the design and safety assessment of the longline aquaculture facility with similar structures and environment conditions in this study.